1985
DOI: 10.1016/0022-2852(85)90297-8
|View full text |Cite
|
Sign up to set email alerts
|

The vapor-phase infrared and Raman spectra of p-difluorobenzene (h4) and (d4)

Abstract: This new study of the vapor-phase infrared and Raman spectra of pdifluorobenzene (h,) and ( 4) includes assignments from the high-resolution electronic spectrum, from fluorescence spectra, and one assignment from the two photon electronic spectrum. A new set of frequencies and assignments has been made for the fundamentals of this important intermediate-sized molecule. The most important changes concern the assignments previously made for the lowfrequency a, mode (us), two members of the &, class (ui9 and YH))… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

1985
1985
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 13 publications
3
11
0
Order By: Relevance
“…The assignments in Ref. [15] largely confirm those made in earlier investigations, but several vibrational wavenumbers are reassigned and this work has been used as the key reference for the S 0 vibrational wavenumbers in later studies. Despite this, we believe several vibrational wavenumbers have been incorrectly assigned in Ref.…”
Section: Para-difluorobenzenesupporting
confidence: 76%
See 4 more Smart Citations
“…The assignments in Ref. [15] largely confirm those made in earlier investigations, but several vibrational wavenumbers are reassigned and this work has been used as the key reference for the S 0 vibrational wavenumbers in later studies. Despite this, we believe several vibrational wavenumbers have been incorrectly assigned in Ref.…”
Section: Para-difluorobenzenesupporting
confidence: 76%
“…The first of which is the vibrational wavenumber assigned to D 24 (which is a b 2u symmetry mode, ν 19 in Mulliken numbering). This vibration was assigned to a wavenumber of 1437 cm -1 in previous work [23], however Zimmerman and Dunn suggested that this could be incorrect if that feature corresponded to one they saw at 1431 cm -1 with the wrong band profile; on this basis they assigned a wavenumber of 1633 cm -1 to this vibration [15]. However, based on calculated vibrational wavenumbers, and through comparison with the wavenumber of this vibration in other para-disubstituted molecules (vide infra), we believe that this assignment is incorrect, while the original assignment fits well with our calculated wavenumber and trends across the series.…”
Section: Para-difluorobenzenementioning
confidence: 93%
See 3 more Smart Citations